Reordenamiento del museo Luis Félix López de la ciudad de Calceta - Huerta Vera, José Fernando (2012)
The research aimed to reorganize the areas of Luis Felix Lopez museum according to its functionality with respect to the availability of physical space. A methodologyc procedure was developed in which structured phases, stages and methods were used in the physical rearrangement, for which it was proceed to evaluate the museum service through a comparative analysis based on the guidelines proposed by the Ecuadorian System of Museums (SIEM). The diagnostic results of the current museum management helped identify new areas, considered usable, designed for the museological service, where it was determined that the ground floor will be used for temporary exhibitions, while in the back where operates the public library, will become a documental center; on the second plant will be located the permanent exhibition. The physical rearrangement of Luis Felix Lopez Museum will allow it to integrate into the local tourist offer of city Calceta, safeguarding the historical and archeological heritage of Canton Bolívar.